Associations between metal constituents of ambient particulate matter and mortality in England: an ecological study. Issue 12 (3rd December 2019) - Lavigne, Aurore; Freni Sterrantino, Anna; Liverani, Silvia; Blangiardo, Marta; de Hoogh, Kees; Molitor, John; Hansell, Anna
Abstract : Objectives: To investigate long-term associations between metal components of particulate matter (PM) and mortality and lung cancer incidence. Design: Small area (ecological) study. Setting: Population living in all wards (~9000 individuals per ward) in the London and Oxford area of England, comprising 13.6 million individuals. Exposure and outcome measures: We used land use regression models originally used in the Transport related Air Pollution and Health Impacts—Integrated Methodologies for Assessing Particulate Matter study to estimate exposure to copper, iron and zinc in ambient air PM. We examined associations of metal exposure with Office for National Statistics mortality data from cardiovascular disease (CVD) and respiratory causes and with lung cancer incidence during 2008–2011. Results: There were 108 478 CVD deaths, 48 483 respiratory deaths and 24 849 incident cases of lung cancer in the study period and area. Using Poisson regression models adjusted for area-level deprivation, tobacco sales and ethnicity, we found associations between cardiovascular mortality and PM2.5 copper with interdecile range (IDR 2.6–5.7 ng/m 3 ) and IDR relative risk (RR) 1.005 (95%CI 1.001 to 1.009) and between respiratory mortality and PM10 zinc (IDR 1135–153 ng/m 3 ) and IDR RR 1.136 (95%CI 1.010 to 1.277). We did not find relevant associations for lung cancer incidence. Metal elements were highly correlated. Conclusion: Our analysis showed small but not fully consistent adverse associations between mortality and particulate metal exposures likely derived from non-tailpipe road traffic emissions (brake and tyre wear), which have previously been associated with increases in inflammatory markers in the blood.